Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd005495.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental intervention programmes post-hospital discharge to prevent motor and cognitive impairments in preterm infants

Abstract: This is a reprint of a Cochrane review, prepared and maintained by The Cochrane Collaboration and published in The Cochrane Library 2012, Issue 12 http://www.thecochranelibrary.com Early developmental intervention programmes post-hospital discharge to prevent motor and cognitive impairments in preterm infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 106 publications
4
160
0
7
Order By: Relevance
“…In early infancy, preterm infants tend to be less attentive, less responsive and need more breaks from interaction than term infants (Wolf, et al, 2002). As these children grow older, they are at risk of learning disabilities, which can in turn affect cognitive, motor and social competencies (Michele A Lobo & Galloway, 2013;Spittle, Orton, Anderson, Boyd, & Doyle, 2012). Studies indicate that preterm infants are also at risk of delayed play skills (Korja, Lehtonen, & Latva, 2012;Vig, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early infancy, preterm infants tend to be less attentive, less responsive and need more breaks from interaction than term infants (Wolf, et al, 2002). As these children grow older, they are at risk of learning disabilities, which can in turn affect cognitive, motor and social competencies (Michele A Lobo & Galloway, 2013;Spittle, Orton, Anderson, Boyd, & Doyle, 2012). Studies indicate that preterm infants are also at risk of delayed play skills (Korja, Lehtonen, & Latva, 2012;Vig, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric physical therapist (PT)s aim to alleviate preterm infants' movement problems, enhance motor development and support the infants' participation in age-appropriate activities (Blauw-Hospers, De Graaf-Peters, Dirks, Bos, & Hadders-Algra, 2007;Campbell, Palisano, & Orlin, 2012;Spittle, et al, 2012). In this work, attention and motivation are key factors for the infants' motor learning, mastery of new skills and sense of self-efficacy (Atun-Einy, Berger, & Scher, 2013;Brodal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first systematic review and metaanalysis that has attempted to define and measure the effect of EE on motor development of infants with CP. Previous systematic reviews have focused more broadly on motor and cognitive outcomes in preterm populations 27 or those at risk for a broader range of developmental disorders. 46,47 In these previous studies, favorable cognitive outcomes programs have been consistently demonstrated for a range of early-intervention programs, but motor outcomes rarely improve.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, training parents to practice specific motor tasks with typically developing infants accelerated the rate of motor development in both the short and long term. 19,20 In the small amount of literature about the benefits of EE for infants at risk for brain injury, we know that premature infants demonstrate neurobehavioral benefits from sensory-specific EE activities, such as massage 21 26,27 Because only ∼8% to 15% of premature infants will go on to have CP, 28 it is not clear whether interventions aimed at preterm infants will have clear benefits for infants with CP. In contrast, "traditional" physical and occupational therapy earlyintervention approaches, such as neurodevelopmental treatment (NDT), have not been shown to be effective in improving motor outcomes in infants or older children with CP, despite the theoretical possibility of providing sensory-enrichment cues for learning motor skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation